2015 7th International IEEE/EMBS Conference on Neural Engineering (NER) 2015
DOI: 10.1109/ner.2015.7146748
|View full text |Cite
|
Sign up to set email alerts
|

A neuromuscular electrical stimulation strategy based on muscle synergy for stroke rehabilitation

Abstract: Recent experiments have suggested that the central nervous system (CNS) makes use of muscle synergies as a neural strategy to simplify the control of a variety of movements by using a single pattern of neural command signal. This nature of muscle coordination could have great significance in the treatment and rehabilitation of upper limb impairments for hemiparetic patients post stroke.The use of neuromuscular electrical stimulation (NMES) for neural prosthetics or therapeutic applications has been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…As well as previous studies have demonstrated that the Central Nervous System (CNS) makes use of muscle synergies as a neural strategy to simplify the control of a variety of movements by using a single pattern of neural command signal [16]. So extracted synergy patterns of this study can be used in rehabilitation [15] and diagnosis [10]. Whether the source of pain in lumber is muscles or not can be determined easily by comparing muscles patterns of healthy subjects with patients who had pain in the lumber [10].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…As well as previous studies have demonstrated that the Central Nervous System (CNS) makes use of muscle synergies as a neural strategy to simplify the control of a variety of movements by using a single pattern of neural command signal [16]. So extracted synergy patterns of this study can be used in rehabilitation [15] and diagnosis [10]. Whether the source of pain in lumber is muscles or not can be determined easily by comparing muscles patterns of healthy subjects with patients who had pain in the lumber [10].…”
Section: Discussionmentioning
confidence: 77%
“…Synergy includes two types of synchronous (constant Synergy and variable coefficients) and Asynchronous (variable synergy and constant coefficients) [14]. Synergy pattern can be used for functional electrical stimulus [15]. Every muscle performance will be divided into linear vectors.…”
Section: Synergymentioning
confidence: 99%
“…Previous studies have demonstrated that the central nervous system (CNS) makes use of muscle synergies as a neural strategy to simplify the control of a variety of movements by using a single pattern of neural command signal. So extracted synergy patterns of this study can be used in rehabilitation (C. Zhuang et al, 2015). That is to say, stimulation with specific patterns can be used instead of mentioned recovery because in some situation athletic cannot use these recovery, for example, in locker room between two half time of competition.…”
Section: Discussionmentioning
confidence: 99%
“…Synergy includes two types of synchronous (constant Synergy and variable coefficients) and Asynchronous (variable synergy and constant coefficients). Synergy pattern can be used for functional electrical stimulus ( Zhuang C et al, 2015). Each muscle performance will be divided into linear vectors, every moment, the sum of these vectors with specific coefficients Reconstruct electromyogram signal.…”
Section: Synergymentioning
confidence: 99%
“…sEMG analysis has been investigated a lot nowadays. Recent experiments have suggested that the central nervous system (CNS) makes use of muscle synergies as a neural strategy to simplify the control of a variety of movements [7]. These synergies can compensate mechanical disabilities, resulting invisible to an external evaluation [8].…”
Section: Introductionmentioning
confidence: 99%